Urban living attitude and a change in environment - Abu Bakar, Aniza (The International Institute of Islamic Thought, 2019)
The world's population is said to have been recorded as having reached the first one billion in around 1800, three billion in 1959, five billion in 1987 (worldometers - online), and the figure keeps on increasin. The current world's population is close to eight billion. As the population grows, more people are migrating to cities. What were once towns have transformed into cities, and then megacities - cities that accommodate over 10 million inhabitants. More rural areas are turning into urban areas. Urbanization is a continuous process that can be horizontally and vertically seen. It involves the changing of the physical landscape following the demand of the ever increasing population. The statistics show that the world's urban population was 30% in 1950, 54% in 2014, and is projected to rise to 66% by 2050 (World Urbanization Prospects - online). Population growth and migration are making an impact on the environment, the economy, and the people, and their quality of life, both in positive and negative ways. More resources are needed to address the needs and demands of the people. For instance, more food is being produced, more products are being innovatively developed to suit the lifestyles, and more services are being provided. Along with these, among others, more energy is being consumed, and the production of solid waste is also increasing. Hence, this article discusses the Islamic perspectives on the environment and its issues and the people's attitude towards urban sustainability.